Antecedents of successful private label business in the Czech retail environment - Trofimchuk, Iuliia; Olšanová, Květa; Neumannová, Pavla; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2019)
The development of private label brands is one of the most promising directions for connection between retailers and customers. Private label brands have grown from cheap second-rate products to the competitors to popular manufacturer brands. This master’s thesis studies customers’ perception of private label brands in the Czech Republic and key success factors which influence customers’ decisions during buying private label brands. It evaluates the relationship between the development of private label brands, the retailers’ strategies and customers’ perception. After an investigation of theoretical review and previous studies of this topic, five research questions have been formulated which helped to analyze the purchasing behaviour of Czech customers towards private label brands (based on quantitative research amongst private labels buyers in the Czech Republic). The key findings of this thesis are determined factors which influence customers' perception of private label brands in the Czech Republic as well as the success of retailers' strategies in this field.
Vedoucí práce: Květa Olšanová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2019
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2019
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses